The Influence of Previous Year's Audit Opinions, Auditor Reputation, Company Growth, and Profitability on Going Concern Audit Opinions - Niken Lestari Putri; Nur Isna Inayati; Eko Haryanto; Edi Joko Setyadi (Universitas Islam Sultan Agung (UNISSULA), Faculty of Economics, Department of Accounting, 2022)
The purpose of this research is to determine how previous audit opinion, auditor reputation, company growth, and profitability affect going concern audit opinion. The sample used in this emperical study was mining companies listed on the Indonesia Stock Exchange in the 2014-2019 period. Purposive sampling was used to collect as many as 29 samples of research firms over the course of six years. The data used was secondary data collected from that Indonesian Stock Exchange and each company's website. The data analysis technique used is logistic regression. The study revealed that auditor reputation opinion and company growth had no effect on going concern audit opinion. While the audit opinion variable in previous years has a significant effect on going concern audit opinion, and the profitability variable had a negative effect on going concern audit opinion. Keywords: Audit Opinion Years Previously, Auditor Reputation, Company Growth, Profitability, and Going Concern Audit Opinion.